Virtual reality in teaching foreign languages - Victoria V. Dobrova; Polina G. Labzina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article analyses the shortcomings of the foreign languages teaching system on different educational levels. At present more attention is paid to the leading role of the language environment and motivation to stimulate the process of foreign languages learning. In this connection the notion of virtual reality and its technologies is revealed. Despite a great potential of virtual reality technologies in education, their application is rare. The analysis of the notion “virtuality” let us distinguish its main features and possibilities making it an ideal educational environment.